The Description of Eating Behavior and Anemia in Adolescents at STIKES â€˜Aisyiyah Yogyakarta - Umi Nadhiroh; Anjarwati Ajarwati (State Islamic University of Sunan Ampel, 2017)
Anemia due to iron deficiency was the most common problem suffered by women. Around 41,4% - 66,7% young womens in Indonesia suffered from anemia. A preliminary study Ã‚ at STIKES Ã¢â‚¬ËœAsyiyah Yogyakarta showed that 7 out of 10 respondents have anemia with 9 of them have good eating habits. One of the reason of iron deficiency caused by their eating behavior. Instead of choosing foods based on the taste rather than nutritional consideration. This condition would affected on the studentÃ¢â‚¬â„¢s concentration ability. The research aim was to find the eating behavior and the anemia cases among adolescents at STIKES Ã¢â‚¬ËœAsyiyah Yogyakarta. . This was a quantitative descriptive research with cross sectional approach. The cluster sampling was used by simple random sampling. The analysis results showed 29 of 30 respondents have good eating behavior but 26 of them have anemia. Based on the finding, the adolescent suggested to put their concern more about the quality and quantity of food that will consume and take blood booster tablets especially during menstruation.